2006
DOI: 10.2304/ciec.2006.7.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Men in the Nursery Revisited: Issues of Male Workers and Professionalism

Abstract: Professionalising the early childhood workforce in terms of improving pay and conditions of work and employing male workers can be seen as independent trends: there is no necessary relationship between the two. However, when the definition of professionalism is extended to include the scope and quality of practice, the experiences and views of male and female workers may have a contribution to make. This article is based on revisiting a study of male and female workers in childcare centres, analysed in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 19 publications
1
38
0
13
Order By: Relevance
“…ECEC remains an almost entirely female workforce' (Van Laere et al 2014, 6). A higher degree of professionalism and better salaries do not automatically lead to an increase of the number of men working in ECEC, as Cameron (2006) and Peeters (2007) concluded before. Research on gender and academization in Germany has shown that the proportion of male students in newly introduced university bachelor courses is not higher than in traditional vocational schools for ECEC workers (Keil, Pasternack, and Thielemann 2013;Rohrmann 2012b).…”
Section: From Care To Education? Academization and Gendermentioning
confidence: 85%
“…ECEC remains an almost entirely female workforce' (Van Laere et al 2014, 6). A higher degree of professionalism and better salaries do not automatically lead to an increase of the number of men working in ECEC, as Cameron (2006) and Peeters (2007) concluded before. Research on gender and academization in Germany has shown that the proportion of male students in newly introduced university bachelor courses is not higher than in traditional vocational schools for ECEC workers (Keil, Pasternack, and Thielemann 2013;Rohrmann 2012b).…”
Section: From Care To Education? Academization and Gendermentioning
confidence: 85%
“…Cameron et al (1999) interviewten 21 ErzieherInnen aus verschiedenen Einrichtungen zu Berufszugängen, ihrer Arbeitssituation und zu ihren Wahrnehmungen von Geschlechterunterschieden im Arbeits-kontext. In der Folge hat die Forschungsgruppe sich für eine bessere Balance der Geschlechter im Arbeitsfeld eingesetzt und weitere Entwicklungen dokumentiert (Cameron 2001(Cameron , 2006Owen 2003 …”
Section: Studien Aus Dem Angloamerikanischen Raumunclassified
“…Professionalism is a socially constructed concept (Osgood, 2006) and, partly for this reason, the term 'profession' and other derivatives have become problematized (Oberhuemer, 1999). Two of the contributory factors to the problematization are that, as previously stated, there is no universal definition of what is meant by 'professional' or 'professionalism' (Cameron, 2006). The literature describes a cluster of related concepts, which is well illustrated in Brock's (2006) seven dimensions of professionalism in ECE: knowledge, education and training, skills, autonomy, values, ethics, and reward.…”
Section: Professionalismmentioning
confidence: 99%